BLACK’S ACTIVISM AND MOVEMENT IN AMERICAN SOCIETY FRAMED IN ANGIE THOMAS’ THE HATE U GIVE: AN INTERSECTIONAL STUDY - Rizqia Nuur Maziyya; Wening Udasmoro (Universitas Gadjah Mada, 2022)
The racial discrimination and oppression toward Black community in the U.S. have become the main concern in American society. Several factors make Black community live with fear and struggle to be accepted in American society. Racial discrimination is a complex phenomenon, which is the accumulation of variables within Black community’s lives. Race, class, and gender are factors that intersect with one another, resulting in continuous racial discrimination toward Black people in the U.S. Black literature explores how Black people encounter oppression and discrimination; and how they fight against them. One of Black young adult literature is entitled The Hate U Give (2017) by Angie Thomas. This novel explores the life of a high school student named Starr who lives within two atmospheres, a black neighborhood and a predominately white school. Through the protagonist’s point of view, this novel explores how the intersection of race, class, and gender are connected and creates continuous racial discrimination in the U.S. Intersectional theory by Patricia Hill Collins is used to investigate how the variables are connected and results in the systemic racism toward Black community. The finding shows how Black people are dealing with racial events in their daily lives, struggle to fight inequality, and attempt to voice their experience through Black activism.